Air–water interfacial properties of enzymatic wheat gluten hydrolyzates determine their foaming behavior. (April 2016) - Wouters, Arno G.B.; Rombouts, Ine; Legein, Marie; Fierens, Ellen; Brijs, Kristof; Blecker, Christophe; Delcour, Jan A.
Abstract: Insight in the link between foaming and interfacial properties of proteins can increase their potential as functional agents in food systems. Here, foaming capacity and stability of structurally different peptic and tryptic wheat gluten hydrolyzates were related to the kinetics of their adsorption at an air–water interface as well as to the properties of a compressed protein film at this interface. Foams from degree of hydrolysis (DH, i.e. the percentage of cleaved peptide bonds) 2 hydrolyzates were more stable than those from their DH 6 counterparts, and this at all protein concentrations tested. However, at protein concentrations from 0.010% to 0.050% (wprot /v), peptic DH 2 and 6 hydrolyzates had better foaming stability than their tryptic counterparts of the same DH. The opposite was observed when protein concentrations ranged from 0.050% to 0.150% (wprot /v). These observations can in part be explained by the molecular mass composition of the samples and, more importantly, by high levels of hydrophobic peptides in the DH 2 samples. The calculation of an average elasticity (up to 20–25 mN/m) from the variation in surface pressure for a variation in surface area in Langmuir isotherms showed that DH 2 samples had higher elasticity than DH 6 samples, which was in agreement with their foaming stabilities at various protein concentrations. Additionally, although not usually considered in literature, it seemed there was a correspondence between surface pressure at different protein surface concentrations and foaming stability at different protein concentrations. Graphical abstract: Highlights: Molecular mass and hydrophobicity define foaming properties of wheat gluten hydrolyzates. Peptides of a certain hydrophobicity play an important role. Differences in foam stability strongly depend on protein concentration. Average protein film elasticity during compression could be related to foaming stability. Langmuir isotherms and foaming stability at varying protein concentrations had similar trends.